2020
DOI: 10.1088/2057-1976/abb981
|View full text |Cite
|
Sign up to set email alerts
|

Infill selection for 3D printed radiotherapy immobilisation devices

Abstract: 3D printing provides new opportunities to create devices used during radiotherapy treatments, yet little is known about the effect process parameters play on the proposed devices. This study investigates the combined influence of infill pattern, infill density and print orientation on surface dose, as well as on the mechanical properties of 3D printed samples, identifying the optimal infill patterns for use in radiotherapy devices including immobilisation. Fused deposition modelling (FDM) was used to produce s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…As a general trend, this study identified that surface dose increased as material thickness increased, similar to previous studies that found increases in surface dose as the density of material increased. 4 , 23 , 24 For an immobilization device, this may suggest using the lowest printable thickness is ideal. However, this would ignore the impact material thickness plays on the mechanical strength of a part, which is critical when used to restrict patient movement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As a general trend, this study identified that surface dose increased as material thickness increased, similar to previous studies that found increases in surface dose as the density of material increased. 4 , 23 , 24 For an immobilization device, this may suggest using the lowest printable thickness is ideal. However, this would ignore the impact material thickness plays on the mechanical strength of a part, which is critical when used to restrict patient movement.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 In order to reduce the toxic side effects of radiation therapy, immobilization devices are used to hold the patient firmly on the treatment couch and minimize exposure of healthy cells to high‐energy radiation beams by keeping the patients in the correct position during the course of treatment. 3 However, these devices can have a bolus effect that increases the radiation dose on the patients’ skin; 4 , 5 , 6 consequently, surface dose measurement is essential to measure the radiation dose on the patient's skin during the course of the treatment. 7 Significant increase in the radiation dose through build‐up effect may lead to painful reddening of the surface tissue.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As highlighted in Tables 4 and 5, the pitch negative masks were identified as the best designs for immobilising the volunteer based on the collected sensor data. (Asfia et al, 2020a), this infill pattern was not available within the Fortus slicing software, and Hexagram was selected as the closest representation of this infill pattern. The full print parameters are presented in Table 6.…”
Section: Mask Optimisationmentioning
confidence: 99%